First the stick, then the carrot? A cross-country evaluation of the OECD's initiative against harmful tax competition - Markus Grottke; Maximilian Kittl (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2016)
In 1998 the OECD launched one of the most comprehensive initiatives ever to combat harmful tax competition. The following paper analyzes how companies' investment activities in tax havens are associated with the three most salient elements of the OECD initiative. Our analysis is based on a U.S. and on a German panel data set. The results suggest that the investment activities of both countries' companies in tax havens are negatively associated with the first element, i.e., the tax havens' public status as being blacklisted. We additionally find that the two subsequent elements of the initiative, that is, the tax havens' commitments to the OECD standards of transparency and the existence of bilateral information exchange agreements, are positively associated with U.S. companies' investment activities in these countries. Unlike the U.S. case, tax havens' commitments are negatively associated with German companies' investment activities, while the evidence is mixed for the case of a bilateral information exchange agreement with Germany. We interpret our findings in the light of reputational effects.
Keywords: H2; H26; H87; 650; Tax havens; OECD blacklisting; TIEA; Companies' investment activities